Pengaruh Kualitas Produk, Keberagaman Produk dan Brand Image Terhadap Kepuasan Pelanggan di Indomaret Kampung Belimbing - Nababan, Zentina; Sitorus, David Humala (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2024)
This research aims to explore the influence of product quality, product diversity and brand image on customer satisfaction at Indomaret Kampung Belimbing. The research method uses a descriptive type with a quantitative approach. The population is individuals who made purchases at Indomaret Kampung Belimbing during 2023, the number of which cannot be known with certainty. As a sample selection method, this research used the Lameshow formula, and finally, 100 respondents were selected through a purposive sampling method. Data analysis involves multiple linear regression, including steps such as data quality tests, classical assumption tests, influence tests, and hypothesis tests. The results of multiple linear regression analysis show that product quality has an influence of 24.0% on customer satisfaction, product diversity has an influence of 22.7%, and brand image has an influence of 22.2%. The coefficient of determination (R2) shows that overall, product quality, product diversity, and brand image can explain 72.3% of the variation in customer satisfaction. The t test and F test confirm that product quality, product diversity and brand image have a positive and significant influence, both partially and simultaneously, on customer satisfaction at Indomaret Kampung Belimbing.